2016
DOI: 10.1371/journal.pone.0158028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Transcriptome of Maize Mature Embryos from Two China Elite Hybrids Zhengdan958 and Anyu5

Abstract: Zhengdan958 and Anyu5 are two elite maize hybrids of China, which manifest similar paternal lines (Chang7-2) but different maternal lines (Zheng58 and Ye478). Zhengdan958 has a 10–15% yield advantage over Anyu5. In this study, we applied digital gene expression technology to analyze transcriptomes of mature embryos from the two hybrids and their parents, aimed to investigate molecular mechanism of heterosis and genetic effects of maternal lines. Results showed that 71.66% and 49.70% of differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Finally, a thiazole biosynthetic Thi4 family enzyme (Q41739) exhibiting high parent abundance in the UENF/UEM01 hybrid was detected. This protein is involved in thiazole biosynthesis and catalyzes the conversion of NAD and glycine to adenosine diphosphate (ADT); Q41739 also functions in hybrid adaptations to various stress conditions and in DNA damage tolerance [ 46 ]. Moreover, many studies have reported that thiamine biosynthesis is up-regulated during plant adaptation responses to abiotic stress, including salt, cold, flooding, heat, drought, and osmotic stress [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a thiazole biosynthetic Thi4 family enzyme (Q41739) exhibiting high parent abundance in the UENF/UEM01 hybrid was detected. This protein is involved in thiazole biosynthesis and catalyzes the conversion of NAD and glycine to adenosine diphosphate (ADT); Q41739 also functions in hybrid adaptations to various stress conditions and in DNA damage tolerance [ 46 ]. Moreover, many studies have reported that thiamine biosynthesis is up-regulated during plant adaptation responses to abiotic stress, including salt, cold, flooding, heat, drought, and osmotic stress [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high-heterosis hybrid Zhengdan 958 has been planted all over China. Its parental inbreeds belong to two different heterotic groups: Zheng 58 belongs to the PA heterotic group, a subgroup of SS, and Chang 7–2 belongs to TSPT heterotic group, a subgroup of NSS (Bai et al, 2015 ; Ma et al, 2016 ). Following the testcross (TC) progeny production scheme (Comstock and Robinson, 1952 ), 174 RILs (F 7 ) derived from the hybrid Zhengdan 958 were used as pollen parents to cross the parental lines Zheng 58 [TC (Zheng 58)] and Chang 7–2 [TC (Chang 7–2)].…”
Section: Methodsmentioning
confidence: 99%
“…This high percentage indicates that the expression divergence of most hybrid genes is not merely a result of the combined effect of allelic expressions, but a consequence of diverse gene expression regulatory mechanisms. A number of recent studies, including in maize [ 46 ], soybeans [ 47 ], rubber trees [ 10 ], interspecific hybrids between Brassica napus and B. rapa [ 48 ], and cauliflower [ 49 ], show a prevalence of non-additive gene action in the hybrids. Non-additive gene expressions may have both direct and indirect contributions to heterosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, hybridization exposes the parental alleles to trans-regulatory factors originating from both parents, and therefore, the differences in allelic regulation may also be due to trans-effects. Numerous studies have shown that non-additive gene expression mainly results from the trans-effects, and may cause the gene expression in the hybrids to deviate significantly from additive expression [ 31 , 46 , 51 , 52 ]. In cabbage hybrids, of the genes showing non-conserved expressions, 39–54% showed cis-effects, compared to only 13–16% showing trans- effects ( Figure 6 a).…”
Section: Discussionmentioning
confidence: 99%